Beyond Stereotypes: A Feminist Reading of Women Characters in R.K. Narayan’s The Guide (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
R.K. Narayan occupies a distinctive position among the most celebrated Indian writers in English. His novels vividly capture the ethos of Indian life and sensibility, often rooted in the fictional town of Malgudi, which serves as a microcosm of South Indian middle-class society. In each of his novel, there is at least one female character who occupies an important place in the story and Rosie is such a female character in The Guide. She represents a modern woman who is educated and ambitions and strives to attain independent economic entity according to her own taste and talent although she has to pay a heavy price for it. The other female characters in the novel are Raju’s mother and Velan’s sister. Raju’s mother represents the conservative and orthodox women who follow tradition and culture. She is a dutiful wife and a loving mother. She serves as both a moral compass and a guardian of values, offering guidance to Raju and Rosie, and eventually withdrawing from the household when her counsel is ignored. Velan’s sister, although a minor character, plays a crucial role in shaping Raju’s transformation into a spiritual figure. This paper is a humble attempt to study this aspect of R.K. Narayan’s characterisation.